West Nile virus outbreak among horses in New York State, 1999 and 2000. - Trock, S C (Centers for Disease Control and Prevention, 2001)
West Nile (WN) virus was identified in the Western Hemisphere in 1999. Along with human encephalitis cases, 20 equine cases of WN virus were detected in 1999 and 23 equine cases in 2000 in New York. During both years, the equine cases occurred after human cases in New York had been identified.